2016
DOI: 10.1016/j.jaci.2015.08.047
|View full text |Cite
|
Sign up to set email alerts
|

A histamine-independent itch pathway is required for allergic ocular itch

Abstract: Non-histaminergic TRPA1 neural pathway is required for the development of allergic ocular itch. Pharmacological inhibition of TRPA1 channel can lead to novel therapeutic strategies to treat ocular itch in severe allergic conjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 14 publications
2
32
0
Order By: Relevance
“…In contrast, TRPV1, as a nociceptive channel, is a more promising drug target than TRPM8 for treating cold allodynia. Our previous studies have shown that antagonizing TRPV1 could effectively block histamine-dependent itch in allergic conjunctivitis 30 , suggesting a potentially wide use of TRPV1 antagonists in alleviating ocular discomforts associated with different ocular conditions. Furthermore, the activation of TRPM8 + /TRPV1 + neurons by cold causes the release of substance P, which has been shown to mediate neurogenic inflammation 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, TRPV1, as a nociceptive channel, is a more promising drug target than TRPM8 for treating cold allodynia. Our previous studies have shown that antagonizing TRPV1 could effectively block histamine-dependent itch in allergic conjunctivitis 30 , suggesting a potentially wide use of TRPV1 antagonists in alleviating ocular discomforts associated with different ocular conditions. Furthermore, the activation of TRPM8 + /TRPV1 + neurons by cold causes the release of substance P, which has been shown to mediate neurogenic inflammation 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has revealed an essential involvement of TRPA1-mediated nonhistaminergic itch pathway in allergic ocular itch 18 . However, TRPA1 is expressed by both nociceptive and itch-sensing neurons 19,20 .…”
Section: Introductionmentioning
confidence: 93%
“…While histamine has known involvement in AC itch, an additional histamine-independent mode of itch induction has recently been elucidated 17 . In a murine model, Huang et al 18 demonstrated that both TRPV1, a histamine-sensitive ion channel, and TRPA1, a histamine-independent ion channel are required for the induction of allergic ocular itch. This finding may explain the limitations of currently available anti-allergy eye drops 19 .…”
Section: Discussionmentioning
confidence: 99%